U-shaped pattern of acoustic emission energy in the accelerated cracking stage of moist mortar at low shear rates - Hongran Chen; Chao Xu; Yuan Cui; Lei Xue; Siqing Qin (Case Studies in Construction Materials)
Laboratory experiments with acoustic emission monitoring are widely used to develop forecasting methods of shear fracture in mortar structures. Nevertheless, significant differences in loading conditions—particularly loading rates and moisture content—between laboratory specimens and in-situ structures have long been overlooked, potentially reducing the practical relevance of experimental findings. Thus far, the acoustic emission pattern during shear cracking process of mortar under field-representative conditions remains elusive. We conducted direct shear experiments on jointed mortar specimens with controlled moisture contents at low shear loading rates to simulate structures’ failures. A special U-shaped pattern of acoustic emission energy temporal distribution, which contains two energy bursts separated by a low-energy quiet period, was observed. The former burst corresponds to accelerated cracking onset and the latter burst signals macro-fracture. The emergence of this pattern is governed by shear cracking in ligaments where shear stress concentrates, facilitated by lower loading rate and moisture content. The anomalous burst at accelerated cracking onset serves as a potential precursor to mortar fracture, and the energy magnitude differences between two bursts remained relatively consistent across experiments. These findings provide crucial insights for bridging laboratory acoustic emission pattern with field observation and establishes a scientific foundation for developing forecasting methods of mortar structure fracture.